New estimates and complications in the assessment of female functional maturity for the European lobster (Homarus gammarus) on the Yorkshire Coast (UK) - James Michael Wood (Journal of Fisheries, 2018)
New estimates of female Homarus gammarus functional maturity were developed from targeted offshore and quayside based industry surveys in the Yorkshire Coast fishery. Offshore surveys also provided the first stock specific quantification of pre-recruit contributions. A contrast in results identified a new complication in estimating functional maturity attributed to ‘soft’ animal exploitation which is reviewed and assessed.